In Defense of Futile Effort – Joanna Rapacka and the Study of Croatian Literary History - Bogdan, Tomislav (Poznańskie Studia Slawistyczne, 2018)
The article analyses two methods from the scholarly oeuvre of a great Polish Croatian and Slavic studies scholar Joanna Rapacka (1939–2000). These two methods are very interesting and in a particular manner topical, especially in Croatian philology: due to a reconstruction of historical poetics and research of sources, and because of a deconstruction of national myths and national essentialism in literary historiography. These two approaches are closely linked in an attempt to understand an older, pre-modern literary culture in its original, epochal context.